2015
DOI: 10.1111/cmi.12468
|View full text |Cite
|
Sign up to set email alerts
|

African swine fever virus assembles a single membrane derived from rupture of the endoplasmic reticulum

Abstract: Collective evidence argues that two members of the nucleocytoplasmic large DNA viruses (NCLDVs) acquire their membrane from open membrane intermediates, postulated to be derived from membrane rupture. We now study membrane acquisition of the NCLDV African swine fever virus. By electron tomography (ET), the virion assembles a single bilayer, derived from open membrane precursors that collect as ribbons in the cytoplasm. Biochemically, lumenal endoplasmic reticulum (ER) proteins are released into the cytosol, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 50 publications
1
44
0
Order By: Relevance
“…The open membrane, which holds the viral DNA, is progressively coated by capsid proteins to form an icosahedral particle, similarly to our observation of AdV capsid fragments engulfing the condensing core. A similar mechanism has been proposed for African swine fever virus (ASFV) [74]. Bacteriophage PM2, ASFV, and Mimivirus, all contain a membrane inside the icosahedral shell.…”
Section: Discussionmentioning
confidence: 73%
“…The open membrane, which holds the viral DNA, is progressively coated by capsid proteins to form an icosahedral particle, similarly to our observation of AdV capsid fragments engulfing the condensing core. A similar mechanism has been proposed for African swine fever virus (ASFV) [74]. Bacteriophage PM2, ASFV, and Mimivirus, all contain a membrane inside the icosahedral shell.…”
Section: Discussionmentioning
confidence: 73%
“…Subsequently, cisternae are ruptured into a dense network of open, single bilayer membrane sheets that accumulate in the centre of the PBCV‐1 factories. These open sheets interact with a capsid protein to form pre‐capsids, as was shown to be the case for Vaccinia (Chlanda et al ., ), Mimivirus (Krijnse‐Locker et al ., ; Mutsafi et al ., ) and ASFV (Suárez et al ., ). Therefore, a general mechanism for the biogenesis of single internal membrane bilayers in viruses, as well as a role for these sheets as templates for crescents formation and capsid assembly, may exist.…”
Section: Discussionmentioning
confidence: 97%
“…The ERGIC and TGN are involved in membrane biogenesis and virogenesis in poxviruses (Schmelz et al 1994, Risco et al 2002, Moss 2015. Detailed studies on the monotypic asfarid NCLDV ASFV have shown that ER is involved in the formation of the lipid internal membrane between the core shell and capsid (Cobbold et al 1996, Andrés et al 1998, 2002, Rouiller et al 1998, Epifano et al 2006, Windsor et al 2012, Salas & Andrés 2013, Suarez et al 2015, possibly due to col- Table 1 Figs. 17-18.…”
Section: Discussionmentioning
confidence: 99%
“…18. Crystalline array of mature nucleocapsids; ×5335 lapsed (Andrés et al 1998) or ruptured (Suarez et al 2015) ER cisternae pushing the 2 membranes together to form a unit-like membrane (Andrés et al 1998). Most NCLDV viruses have a membrane that separates the nucleocapsid from the external capsid (Xiao & Rossmann 2011), including LCDV (Heppell & Berthiaume 1992), and host membranes probably serve as a scaffold to which capsid and shell proteins bind (Chinchar et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation